Comparative analysis of three various chemotherapy protocols for acute lymphoblastic leukemia BFM-90m, MB-91 and PECO-92 in Moscow and St.-Petersburg - E. G. Boichenko; E. M. Petrova; M. B. Ivanovskaya; I. A. Garbusova; M. B. Belogurova; G. G. Radulesku; Yu. V. Roumiantseva; D. V. Litvinov; S. N. Lagoiko; K. L. Kondratchik; N. I. Ponomareva; N. R. Tukalova; et al. (Онкогематология)
Comparative retrospective analysis of treatment results of three different chemotherapy protocols - ALL BFM 90m, ALL MB 91 and PECO 92 — in primary ALL patients aged before 18 years, registered in Moscow and St-Petersburg clinics from 01.01.1993 to 01.01.1999 is presented. It has been shown, that treatment results of PECO 92 protocol have appeared much worse, thus, any differences in treatment results for children with ALL between ALL BFM 90m and ALL MB 91 protocols were not revealed. Event-free survival (pEFS) of St-Petersburg' patients, received PECO 92 protocol (60±3%), was significantly worse, in comparison with patients treated according to ALL BFM 90m protocol (74±4%; р=0,0056) and ALL MB 91 protocol (73±4%; р=0,0239). The high incidence of relapses became a main cause of efficacy decreasing. Differences of induction and remission death incidences between three chemotherapy protocols were not revealed. Significant and most expressive EFS differences between PECO-92 and two other protocols were obtained in boys, in a 1—10 age group, and in patients with leukocytes count > 100 000/mm3, in patients with non-T-ALL and in patients with spleen size >4 cm.